Redescription of the fig wasp genus Sycophilodes Joseph (Chalcidoidea: Pteromalidae: Epichrysomallinae) with description of a new species from India - Pramanik, Achintya; Dey, Debjani (Zootaxa, 2014)
Sycophilodes Joseph is a non-pollinating fig wasp genus so far reported only from Ficus benghalensis L. The genus Sycophilodes is revised with redescription of the male and the first description of the female of its only currently included species, S. moniliformis. A second species, Sycophilodes uluberiaensis Pramanik & Dey sp. nov. is described. Available keys are modified and supplemented to facilitate identification of Sycophilodes and a key for distinguishing both sexes of the two included species is presented. All type specimens are deposited in the National Pusa Collection, IARI, New Delhi.